The challenges of ozone therapy and access to sources of information (Ozone Therapy Global Journal, 2014)
Ozone therapy is today a general medical practice in various countries. A solid basicand clinical research supports the implementation of this procedure. However, for manyprofessionals worldwide it is unknown, tending to classify it as a fraudulent therapyand sometimes dangerous. These comments are so lacking in argument that if theywere not made by professionals one could argue that they are ' gossip '